Community Empowerment in an Effort to Increase Immunity during the COVID-19 Pandemic: Pemberdayaan Masyarakat dalam Upaya Meningkatkan Imun di Masa Pandemi COVID-19 - Halim, Aisyah Nabilah; Novianti, Chyndi Dwi; Insanni, Intan; Cholifah, Siti (Procedia of Social Sciences and Humanities, 2022)
The COVID-19 pandemic has caused various health problems to be twice as likely to die. Paying attention to one's health means also caring about the health of others, such as by helping each other and working together to increase immunity to stay healthy and fit during the COVID-19 pandemic. Judging from the state of the environment and the potential of its citizens, it then produces efforts that can be done together to maintain and improve the immunity of the Kebonsari village community, namely by planting and utilizing Family Medicinal Plants (TOGA) and using massage techniques at acupressure points. TOGA is an efficacious plant as a natural medicine that is easily obtained and cultivated in the yard of residents' houses. Utilizing massage techniques on acupressure points on the body and fingers can relieve the pain that is being felt. Combining herbal ingredients from TOGA results and acupressure massage can naturally increase immunity. The socialization procurement process begins with a survey to partner locations and determines the solution that will be provided, then establishes cooperation with village officials and PKK women. The service team provided materials through an LCD projector and distributed leaflets in the form of copies of the materials. The results of community service in the form of socialization totaling 15 participants with initial data, namely, a total of 4 participants (26%) previously had little knowledge about TOGA and acupressure and 11 participants (73%) did not know TOGA and acupressure. After being given TOGA and acupressure socialization, 11 participants (73%) had knowledge about the use of TOGA and acupressure to increase immunity, and 4 participants (26%) could make herbal concoctions and practice acupressure massage on themselves and others correctly.